যদি, \(x=\sqrt3+\sqrt2, y=\cfrac{1}{x}\) হয় তবে \((x+\cfrac{1}{x})^2+(\cfrac{1}{y}-y)^2=\) কত ?
Madhyamik 2024
\(y=\cfrac{1}{x}=\cfrac{1}{\sqrt3+\sqrt2}\)
\(=\cfrac{(\sqrt3-\sqrt2)}{(\sqrt3+\sqrt2)(\sqrt3-\sqrt2)}\)
\(=\cfrac{(\sqrt3-\sqrt2)}{(\sqrt3)^2-(\sqrt2)^2}\)
\(=\cfrac{(\sqrt3-\sqrt2)}{3-2}\)
\(=\sqrt3-\sqrt2\)
আবার যেহেতু, \(y=\cfrac{1}{x}\) সুতরাং, \(x=\cfrac{1}{y}\)
\((x+\cfrac{1}{x})^2+(\cfrac{1}{y}-y)^2\)
\(=(x+y)^2+(x-y)^2\)
\(=(\sqrt3+\sqrt2+\sqrt3-\sqrt2)^2+(\sqrt3+\sqrt2-\sqrt3+\sqrt2)^2\)
\(=(2\sqrt3)^2+(2\sqrt2)^2\)
\(=12+8\)
\(=20\) [Answer]